Association of β-Blocker Therapy at Discharge with Clinical Outcomes after Acute Coronary Syndrome in Patients without Heart Failure - Yan Chen; Xiao-fang Tang; Run-lin Gao; Yue-jin Yang; Bo Xu; Jin-qing Yuan (Cardiovascular Therapeutics)
Aim. To evaluate the clinical impact of β-blocker in patients with adequate left ventricular ejection function (LVEF) who underwent percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS). Methods. A total of 10,724 consecutive patients who underwent PCI throughout 2013 were prospectively enrolled in the study. Among these, we analyzed 5,631 ACS patients who were discharged with LVEF≥40%. Patients were then compared according to the β-blocker prescription at discharge. Results. During a 2-year follow-up, no significant association was observed of β-blocker use with all-cause mortality (with β-blockers 47/5,043 (0.9%) vs. without β-blocker use 8/588 (1.4%); hazard ratio (HR) 0.762, 95% confidence interval 0.36 to 1.64; P=0.485), cardiac death, myocardial infarction (MI), or major adverse cardiovascular and cerebrovascular events. Subgroup analysis demonstrated that the β-blocker use at discharge reduced the 2-year mortality in patients with unstable angina (UA) (HR 0.42, 95% CI 0.19 to 0.94, P=0.034). Landmark analysis at 1 year showed that patients with UA who were discharged with β-blockers had lower mortality (HR 0.17, 95% CI 0.04-0.65, P=0.010) and cardiac death (HR 0.12, 95% CI 0.01-0.99, P=0.049) than those discharged without β-blockers. However, the benefit was lost beyond 1 year. No differences in outcomes were recorded in the AMI or overall population. Conclusions. We present that β-blocker significantly lowers the rate of all-cause death up to 1 year, in UA patients who have undergone PCI and have adequate LVEF. Its role in patients with AMI also deserves further exploration.